The Lived Experiences and Perceptions of Public-School Employee in the Philippines: A PWD’s Perspective - Avila, Philip Gail; Osea, Eleanor; Gata, Ramona; Portea, Jackielene; De Leon, Natividad; Avila, Elda (International Journal of Business, Law, and Education, 2023)
This study aimed to explore and describe the lived experiences of PWD employees in different designations; wherein, Administrative or School Head, Teacher, and Non-teaching or office personnel are the participants of the study. It was conducted at Northeastern part of the Philippines, specifically at region 4A and region V in the Philippines. The paper is qualitative type of research that utilized the van Kaam method of analysis as modified by Moustakas. The study verified the challenges encountered by PWD employees in their workplaces, the experiences and challenges were further categorized into "Work Experience of PWD" and "Challenges as PWD employee." Also, the result show negative and positive perceptions toward the organization. Moreover, the study suggests programs to empower the PWD employees in the Department of Education and how to improve the conditions of PWD employees in Public Schools in the Philippines.